TEACHER FEEDBACK ON STUDENTS’ DESCRIPTIVE TEXT AT MTS ALKHAIRAAT SANDANA - Inda Indrawati; Indah ariyanti hanapi (Jurnal Madako Education, 2022)
The purpose of this study is to find out how a teacher provides feedback to students on descriptive text learning and to determine student responses to teacher feedback. The design in this study used descriptive qualitative research. The subjects in this study were one English teacher and twenty-seven students. The research instrument uses a questionnaire, interviews and documentation. Data analysis in this study is a qualitative analysis with three stages, namely data reduction, data presentation and conclusion drawing/verification. The results of the study based on interviews and questionnaires as supporting the results of the study showed that the English teacher gave direct feedback, namely the teacher gave explanations and questions during the learning process and indirect feedback, namely the teacher gave assignments from the conclusions at the end of learning to students in descriptive text learning. Student responses to teacher feedback in descriptive text learning are quite good by asking, answering and doing the tasks given by the teacher.